1988
DOI: 10.1161/01.cir.77.6.1238
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lp(a) level as a predictor of vein graft stenosis after coronary artery bypass surgery in patients.

Abstract: Although the serum lipoprotein fraction Lp(a) has been associated with coronary artery atherosclerosis, its relationship to narrowing of saphenous vein grafts has not previously been elucidated. We therefore measured serum Lp(a) levels in 167 symptomatic patients undergoing cardiac catheterization who had had coronary artery bypass surgery 0.7 to 14.3 years earlier. Lp(a), total cholesterol, and total triglyceride levels were compared with the degree of saphenous vein graft stenosis to test for any association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
3
3

Year Published

1992
1992
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(72 citation statements)
references
References 34 publications
2
64
3
3
Order By: Relevance
“…1,2) Many risk factors responsible for SVG disease, including smoking, elevated levels of cholesterol, diabetes and longer intervals after CABG, have been identified. [3][4][5] In this study, we have demonstrated for the first time that homocysteine levels were significantly higher in the vein graft disease group than in the no-vein graft disease group, indicating that elevated levels of plasma homocysteine are an independent risk for SVG disease.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…1,2) Many risk factors responsible for SVG disease, including smoking, elevated levels of cholesterol, diabetes and longer intervals after CABG, have been identified. [3][4][5] In this study, we have demonstrated for the first time that homocysteine levels were significantly higher in the vein graft disease group than in the no-vein graft disease group, indicating that elevated levels of plasma homocysteine are an independent risk for SVG disease.…”
Section: Discussionmentioning
confidence: 55%
“…[3][4][5]36,37) In the present study, in addition to high levels of homocysteine, low levels of high-density lipoprotein cholesterol and longer intervals between bypass surgery and coronary angiography were considered to be risk factors for SVG disease. In contrast, low-density lipoprotein cholesterol has no significant relation with SVG disease in this study because levels of low-density lipoprotein cholesterol were controlled by lipid lowering drugs in 64% of all subjects.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In a study of patients with a history of CABG undergoing coronary angiography, Hoff et al (28) found a linear correlation between degree of graft stenosis and the serum lipoprotein(a) level. At approximately the same time, the Cholesterol Lowering Atherosclerosis Study (CLAS) (29,30) assessed the benefits of lowering LDL and raising HDL on angiographic disease progression in vein grafts as well as native coronary arteries.…”
Section: Lipid-lowering Therapymentioning
confidence: 99%
“…4 Genetic factors are the principal determinants of plasma Lp(a) concentrations 5,6 via differences in apolipoprotein(a) polymorphisms between individuals and races. Other factors such as diet, exercise, body mass, gender 7 and probably insulin levels 8 have, however, been shown to be important determinants of Lp(a) concentrations as well; although probably not quantitatively as important as the genetic determinant.…”
Section: Introductionmentioning
confidence: 99%